Exploring the epidemiological role of the Eurasian lynx (Lynx lynx) in the life cycle of Toxoplasma gondii - Scherrer, Patrick; Ryser-Degiorgis, Marie-Pierre; Marti, Iris A.; Borel, Stéphanie; Frey, Caroline F.; Mueller, Norbert; Ruetten, Maja; Basso, Walter (International Journal for Parasitology: Parasites and Wildlife, 2023)
Toxoplasma gondii is a successful coccidian parasite able to infect all warm-blooded animals and humans, causing one of the most common zoonoses worldwide. The Eurasian lynx (Lynx lynx) is one of the feline potential hosts of T. gondii in Switzerland, but little is known about its epidemiological role as a definitive or intermediate host. Serum samples from 183 Eurasian lynx collected from 2002 to 2021 were tested for antibodies to T. gondii by ELISA, IFAT and in case of inconclusive results, immunoblot. Antibodies to T. gondii were found in 150 of 183 (82%) Eurasian lynx. Older age, good health status and a low-altitude habitat were found to be significant predictors for seropositivity. T. gondii oocysts were detected in 3 of 176 (1.7%) faecal samples, indicating the Eurasian lynx as a definitive host. In addition, T. gondii DNA was detected in skeletal muscle (7/88), heart muscle (2/26) and/or brain tissue (2/36) from 10 different lynx by real-time PCR. In one animal, a T. gondii-like tissue cyst was observed in heart muscle and confirmed as T. gondii by immunohistochemistry (1/20) and real-time PCR. With an adapted nested-PCR-multilocus-sequence typing (MLST) and in silico restriction-fragment-lengthpolymorphism analysis (RFLP) approach two different T. gondii genotypes were detected: a lineage II variant (ToxoDB #3) in three animals (two oocyst samples and one heart muscle sample) and a novel genotype exhibiting both type II and III alleles in a further animal (skeletal muscle). The present results indicate that T. gondii infection is widespread in the Swiss lynx population. The Eurasian lynx may contribute to environmental contamination with oocysts and is able to harbour the parasite in different tissues. Genotyping revealed the presence of both a common T. gondii lineage in Europe and a previously unknown genotype and thus shedding more light on the complex molecular epidemiology of T. gondii.